2006
DOI: 10.1177/153537020623100818
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Bioactivity of the Tolerogenic Cytokines, Interleukin-10 and Transforming Growth Factor-β, in the Blood of Acutely Malnourished Weanling Mice

Abstract: The main objective of this investigation was to determine the influence of acute deficits of protein and energy on the blood levels of interleukin-10 (IL-10) and transforming growth factor-beta (TGF-beta), physiologically the main anti-inflammatory and tolerogenic cytokines. In four 14-day experiments, male and female C57BL/6J mice, initially 19 days old, consumed a complete purified diet either ad libitum or in restricted daily quantities, or had free access to an isocaloric purified low-protein diet. A zero-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(80 citation statements)
references
References 47 publications
9
71
0
Order By: Relevance
“…Initial body weights did not differ among groups, and the food intakes and gains in fat and lean tissue exhibited by the age-matched control group were comparable with previous results pertaining to C57BL/6J weanlings given free access to the same complete purified diet [12,[19][20][21]25,29,30]. In addition, the malnutrition pathologies produced in this investigation were comparable with the pathologies reported in previous studies demonstrating a Type 2 cytokine-polarized serum immunoglobulin profile [12] and depression in adaptive cell-mediated inflammatory competence [18,21,25] in the same experimental systems.…”
Section: The 14-day Malnutrition Protocols Elicited Distinct Weight-lsupporting
confidence: 88%
See 1 more Smart Citation
“…Initial body weights did not differ among groups, and the food intakes and gains in fat and lean tissue exhibited by the age-matched control group were comparable with previous results pertaining to C57BL/6J weanlings given free access to the same complete purified diet [12,[19][20][21]25,29,30]. In addition, the malnutrition pathologies produced in this investigation were comparable with the pathologies reported in previous studies demonstrating a Type 2 cytokine-polarized serum immunoglobulin profile [12] and depression in adaptive cell-mediated inflammatory competence [18,21,25] in the same experimental systems.…”
Section: The 14-day Malnutrition Protocols Elicited Distinct Weight-lsupporting
confidence: 88%
“…It was pointed out elsewhere [12,21,23,26,29,30] that the lowprotein model of dietary imbalance used herein mimics essential features of incipient kwashiorkor, whereas the restricted-intake protocol reproduces critical features of marasmus. As expected of a model of incipient kwashiorkor [12,21,23,26,29,30], the carcass fat decrement of the 26-day low-protein model did not reach the extent of loss seen in the 14-day restricted-intake system, at least according to inspection of the results shown in Tables 1 and 2.…”
Section: 3mentioning
confidence: 94%
“…30 This proposition is based on the high blood levels of transforming growth factor-␤, 30 IL-10, 30 and glucocorticoid hormones 2,27 reported in acute prepubescent deficits of energy and/or protein coupled with evidence that these molecules are potent physiological regulators of dendritic cell maturation. 10 In the present investigation, however, the JAWS II cells evidently achieved antigen-presenting maturity after adoptive transfer regardless of the nutritional status of the recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Hillyer et al [27] showed elevated bioactivity of TGF-β, in the blood of acutely protein and energy malnourished weanling C57BL/6J mice. Glucose starvation may also lead to effects on signalling.…”
Section: Interactions With Genotypementioning
confidence: 99%